(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
Applied Behavior Analysis (ABA) interventions for individuals with autism constitutes an influential domain in the USA, and its effectiveness is widely recognized. Understanding the contingencies that operate in this professional environment and practices that have been producing success as a consequence can bring benefits to other environments, including the Brazilian scientific community. The purpose of this article is to present a brief narrative of historical landmarks and practices described in influential American academic readings, with emphasis in the academic training and practices related to ABA interventions for individuals with autism. Issues related to the evolution of the field in Brazil are discussed.